Renewable energy and decentralized power generation in Russia: An opportunity for German-Russian energy cooperation - Denis Chukanov; Petra Opitz; Maria Pastukhova; Gianguido Piani; Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2017)
Renewable and decentralized power generation are a centerpiece of Germany's domestic energy transition (Energiewende) and a major element of its international efforts to pro-mote this goal. Recently, the renewables sector has also been advancing in Russia, albeit from a lower level. Thus, it is time to explore the status quo and analyze the potential for sustainable energy cooperation. In the context of the current deterioration in EU-Russian (energy) relations, crafting a sustainable energy partnership that is based on innovation, with an emphasis on electricity cooperation, might present an added value.
Keywords: 320